PENGEMBANGAN BAHAN BAKU KERAMIK BERPORI UNTUK PENAMBAHAN TARIF PELAYANAN PADA BTIKK TAHUN 2019 - I Nyoman Normal; Ni Nyoman Nurani (Forum Manajemen STIMI Handayani Denpasar, 2020)
The aims of this research were to: evaluate the recent ceramic raw material tariff, make the porous ceramic raw material alternative, select the porous ceramic raw material alternative, and propose the best porous ceramic raw material tariff with its financial variable as a new tariff. The research results shew that : the ceramic raw material service tariff according to Govermental Regulation Number 51 year 2018 is not enaough, because it followed by two tariff, that is : Rp 4.500,-each kg (white ceramic) and Rp 4.200,- each kg (stoneware ceramic), so the demand about glazur, castle mass, porous ceramic raw material, and others are nothing in the tariff. The development of porous ceramic raw material have been done by BTIKK which produce many compositon, that is : darkam-1 (75% Darmasaba clay : 25% husk), darkam-2 (70% Darmasaba clay : 30% husk), darkam-3 (65% Darmasaba clay : 35% husk), and darkam-4 (60% Darmasaba clay : 40% husk). The porous ceramic raw material with darkam-2 composition have been proposed as service addition to increase non tax revenue for BTIKK, because it closer to the requirements of raw material standard, it has been made water filter pot, it use Bali local raw material, and it result the economies cost of good manufactured. The financial variable of darkam-2 porous ceramic raw material followed by : cost of good manufactured Rp 3.858,73, cost price Rp 4.244,60, and operating profit margin Rp 308,70 each kg.